Teknik Penyembunyian dan Enkripsi Pesan pada Citra Digital dengan Kombinasi Metode LSB dan RSA - Antonius Erick Handoyo; De Rosal Ignatius Moses Setiadi; Eko Hari Rachmawanto; Christy Atika Sari; Ajib Susanto (Jurnal Teknologi dan Sistem Komputer, 2018)
This study proposed a combination of steganography and cryptography techniques using LSB and RSA methods. RSA is a popular cryptographic technique that can be applied to digital imagery. Digital image pixel values range from 0 to 255, making the keys used in RSA limited enough and less secure. So in this study, it is proposed to convert pixel image value to 16 bits so that the key used can be more varied. Experimental results proved that there was a steady increase in security and imperceptibility. This was shown by the results of PSNR 57.2258dB and MSE 0.1232dB. This method was also resistant to salt and pepper attacks.